Distribution characteristics and stability of soil aggregates as compounded by soft rock and sand under different planting years of corn in Mu Us sandy land in China - Haiou, Zhang; Zhen, Guo; Chendi, Shi; Juan, Li (Bangladesh Journal of Botany, 2021)
Field plot experiments of compound soil mixing with soft rock and sand with ratios of 1 : 1, 1 : 2 and 1 : 5 during 2010-2018 years of corn cultivation in Mu Us Sandy Land in china., was carried out to observe the change characteristics of composition, distribution and mean weight diameter (MWD) of compound soil water stable aggregate (WSA) under different corn planting years. The results showed that with the increase of planting years, the content of WSA in composite soils of three portions with a particle size of < 0.25 mm gradually decreased, and WSA with a particle size of > 0.25 mm showed a continuous increasing trend. The WSA with a particle size of 0.25 - 0.5 mm accounted high for the maximum ratio, which plays an important role in the agglomeration of the compound soil. After 9 years of planting, the MWD of 1 : 1, 1 : 2 and 1 : 5 compound soil WSA increased by 1.13, 1.85 and 1.58 times, respectively, and t 1:2 compound soil WSA with particle size > 0.25 mm and MWD increase at a faster rate, which lead to a higher soil agglomeration and stability. The interaction between the mixture ratio of soft rock to sand and the planting years of corn has a significant impact on the formation and stability of WSA in the compound soil. With the increase of planting years of corn, the agglomeration effect of compound soil in different proportions was found to enhance, and the development of soil structure improve continuously. Bangladesh J. Bot. 50(3): 917-923, 2021 (September) Special